Bioproduction of a Therapeutic Vaccine Against Human Papillomavirus in Tomato Hairy Root Cultures - Massa, Silvia; Paolini, Francesca; Marino, Carmela; Franconi, Rosella; Venuti, Aldo (Frontiers in Plant Science, 2019)
Human Papillomavirus tumor disease is a critical public health problem worldwide, especially in the Developing Countries. The recognized pathogenic function of E5, E6 and E7 onco-proteins, offer the opportunity to devise therapeutic vaccines based on engineered recombinant proteins. The potential of plants to manufacture engineered compounds for pharmaceutical purposes, from small to complex protein molecules, allows the expression of HPV antigens and, possibly, the regulation of immune functions to develop very specific therapies also as a reinforcement to available nonspecific therapies and preventive vaccination also in Developed Countries. Among plant-based expression formats, hairy root cultures are a robust platform combining the benefits of eukaryotic plant-based bioreactors, with those typical of cell cultures. In this work, to devise an experimental therapeutic vaccine against HPV, hairy root cultures were used to express a harmless form of the HPV type 16 E7 protein (E7*) fused to SAPKQ, a non-cytotoxic form of the saporin protein from Saponaria officinalis, that we had shown to improve E7-specific cell-mediated responses as a fusion E7*-SAPKQ DNA vaccine. Hairy root clones expressing the E7*-SAPKQ candidate vaccine were obtained upon infection of leaf disks of Solanum lycopersicum using a recombinant plant expression vector. Yield was approximately 35,5 μg/g of fresh weight. Mouse immunization with vaccine-containing crude extracts was performed together with immunological and biological tests to investigate immune responses and anticancer activity, respectively. Animals were primed with either E7*-SAPKQ DNA-based vaccine or E7*-SAPKQ root extract-based vaccine and boosted with the same (homologous schedule) or with the other vaccine preparation (heterologous schedule) in the context of TC-1 experimental mouse model of HPV-associated tumor. All the formulations exhibited an immunological response associated to anti-cancer activity. In particular, DNA as prime and hairy root extract as boost demonstrated the highest efficacy. This work, based on the development of low-cost technologies, highlights the suitability of hairy root cultures as possible biofactories of therapeutic HPV vaccines and underlines the importance of the synergic combination of treatment modalities for future developments in this field